Assessment of Water Quality of Shatt al Arab River in north of Basra - Abbass, Roaa H.; Abdul-Hussan, Jabbar Kh; Resen, Amjed K. (Iraqi Journal of Aquaculture, 2022)
The present study was aimed to ecological evolution for the north part of Shatt Al Arab River, by using water quality index (WQI, Canadian Model) because the efficiency of this method to volutes fresh water quality and to determinate the water quality for different uses. This study has been done through the period between December, 2012 to November, 2013; samples were collected monthly during low tide, three stations have been chosen, the first one was near Al Hartha area, the second station was near Al Hartha area and the third station was near Saeed Ali Al Noor Bridge. The present results were showed that water temperature were ranged between 13.8 ºC – 37 ºC and dissolved solids were 100—1670 mg/l, , salinity range were 0.6-2.5 ‰, the range of dissolved oxygen was 5.7-10.7 mg/l, the hardness value was range between 500-1120 mg magnesium ions was 35-93 mg/l, nitrite was 3.5-15 μg nitrogen atom-nitrate/l, the range of phosphate was 0.05-0.5 μg phosphor atom-phosphate /l, phosphorous range was 158-536 mg/l, the range number of faucal bacterial colon was 21-495 CFU/100ml. Water quality index values (WQI) for all study stations, the range was 47-67, these were classified between third (Fair) and fourth (Marginal) categories. Classification of stations was fair for the first station and marginal for the second and third stations.